FINANCIAMENTO À PESQUISA: A VANTAGEM COMPETITIVA ANALISADA SOB A ÓTICA DA VISÃO BASEADA EM RECURSOS - Vilmar Siewert Junior (Revista Gestão Universitária na América Latina, 2019)
In higher education, universities find themselves in a competitive environment. The purpose of this article was to analyze resources that can be a source of competitive advantage for obtaining funding for research in federal public universities in the southern region of Brazil. Through semi-structured interviews with teachers / researchers from four universities, seven resources were analyzed: a) Researchers; b) Relationships of the researcher; c) Research support structure; d) Reputation of the University; e) Evaluation of CAPES; f) University relationships; and g) Physical structure of the University. The competitive advantage was analyzed through the Resource Based View (RBV). The researcher, and all of his know-how, is critical to getting funding, according to his ability and ability there are greater chances of obtaining funding for research. The existence of a research support structure, providing technical and operational support to the researcher, allows the researcher to spend more time analyzing and elaborating the results. Relationships, whether from researchers or universities, allow researchers to have more access to funding sources, expanding the frontier in which they can seek resources. The university's reputation and the CAPES assessment are interlocking resources, a better reputation may be associated with a better CAPES assessment, making it easier for researchers to access funding sources. All these resources generate some type of competitive advantage to the researchers, only for the physical structure no evidence was found that could generate competitive advantage in this context.